Programmation orientee objet appliquee a Ia methode des elements finis : derivations symboliques, programmation automatique - Eyheramendy, Dominique; Zimmermann, Thomas (European Journal of Computational Mechanics, 1995)
New technologies in computer science applied to numerical computations allow new approaches of mechanical problems. The development of object-oriented programming leads to better structured codes for the finite element method and facilitates development and maintainability. The purpose of this paper is to extend the object-oriented approach to the symbolic derivation and automatic of the elemental matrix fonns of the finite element method.